2004
DOI: 10.1002/chem.200305610
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the Solubilization Capacity of Water in Triton X‐100/Cyclohexane/Water System by Compressed Gases

Abstract: The effect of compressed CO2 and ethylene on the properties of Triton X-100/cyclohexane/water systems was studied at different temperatures and pressures. Surprisingly, it was discovered that the compressed gases had the functions of co-surfactants. At suitable pressures, the water-to-surfactant molar ratio (W0) was enhanced significantly by the dissolution of the gas in the solution. The microenvironment in the reverse micelles was investigated by UV-visible spectroscopy by using methyl orange (MO) as a probe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 59 publications
2
24
0
Order By: Relevance
“…The reason is that CO 2 can penetrate into the interfacial film of the reverse micelles and stabilize them by increasing the rigidity of the micelle interlayer, thus reducing the attractive interaction between the droplets. [39] Interestingly, the X CO 2 value corresponding to the minimum cmc point in Figure 3 is consistent with the X CO 2 value at which the w 0 max value occurs. We can deduce that CO 2 in the solution affects the cmc value in two opposite ways.…”
Section: Wwwchemeurjorgsupporting
confidence: 73%
See 1 more Smart Citation
“…The reason is that CO 2 can penetrate into the interfacial film of the reverse micelles and stabilize them by increasing the rigidity of the micelle interlayer, thus reducing the attractive interaction between the droplets. [39] Interestingly, the X CO 2 value corresponding to the minimum cmc point in Figure 3 is consistent with the X CO 2 value at which the w 0 max value occurs. We can deduce that CO 2 in the solution affects the cmc value in two opposite ways.…”
Section: Wwwchemeurjorgsupporting
confidence: 73%
“…[36][37][38] Our previous work showed that compressed CO 2 and ethylene can increase the solubilization capacity of water in sodium bis-2-ethylhexylsulfosuccinate (AOT) and Triton X-100 reverse-micellar systems at suitable pressures because the gases can insert into the interfacial region to enhance the rigidity of the interface layers and reduce the interdroplet attraction. [39][40][41] The tuning and control of the properties of micellar solutions with compressed CO 2 is a very interesting topic. The critical micelle concentration (cmc) and aggregation number are two of the most important characteristics of reverse-micellar solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Because the presence of salinity in the micelle cores can vary the attractive interdroplet interaction and interfacial bending stress [4], it is difficult to distinguish whether the increase of salinity that originates from ionization of CO 2 is a main reason or not for stabilization of the reverse micelles. Generally, the solubility of ethylene in water is extremely small under moderate conditions because of the significant difference in structure and polarity of water and ethylene [14][15][16], while ethylene can increase the solubility of water in a nonionic surfactant (TX-100) reverse micellar system [17]. In this paper, we investigated the effect of compressed ethylene on the solubilization capacity of water in the reverse micelles of AOT in longer-chain alkanes, and the microenvironments of the reverse micelles in the presence of the compressed gas were studied by conductivity measurement and UV-vis technique.…”
Section: Introductionmentioning
confidence: 99%
“…Compressed CO 2 has been used in different fields, such as extraction and fractionation, [12] chemical reactions, [13] materials science, [14] microelectronics, [15] and for the control over the stability of micelles [16] that inhibit the precipitation of surfactants in vesicular systems, [17] the induction of nanoemulsions, [18] the transition between liquid crystals and micelles, [19] the creation of micro-…”
Section: Introductionmentioning
confidence: 99%